Effective development and resilience building: The EU and NATO perspective compared - George-Mihael Manea (CES Working Papers, 2017)
The EU and NATO represent two entities in charge of the protection and self-sufficiency of their communities, being engaged in development activities and resilient-oriented projects at various levels. Despite their different approach on effective development and resilience building, their mission has convergent aspects in order to ensure that the EU development goals impact the selfsufficiency of a household and the NATO agreed baseline requirements improve the level of civil preparedness and protection within the communities. Development and civil protection put the EU and NATO in the middle of the puzzle, providing technical expertise and tailored assistance for the countries in need, as well as to identify and anticipate possible vulnerabilities that might occur in both developing and developed countries. The role played by both the EU and NATO on the world stage come to highlight the importance that the two actors bring in the actual unpredictable environments.
Keywords: 330; resilience; development; community; EU; NATO